The chemokine (C-C motif) ligand protein synthesis inhibitor bindarit prevents cytoskeletal rearrangement and contraction of human mesangial cells. (September 2016) - Paccosi, Sara; Giachi, Matelda; Di Gennaro, Paola; Guglielmotti, Angelo; Parenti, Astrid
Graphical abstract: Highlights: Cellular mechanisms responsible of mesangial cell dysfunction were investigated. Bindarit inhibited mesangial cell contraction induced by AngII, ET1 and TGFβ. Bindarit inhibited vinculin organization and phosphorylation. Bindarit displays mesangial protective effects in response to AngII, ET1 and TGFβ. Abstract: Intraglomerular mesangial cells (MCs) maintain structural and functional integrity of renal glomerular microcirculation and homeostasis of mesangial matrix. Following different types of injury, MCs change their phenotype upregulating the expression of α-smooth muscle actin (α-SMA), changing contractile abilities and increasing the production of matrix proteins, chemokines and cytokines. CCL2 is a chemokine known to be involved in the pathogenesis of renal diseases. Its glomerular upregulation correlates with the extent of renal damage. Bindarit is an indazolic derivative endowed with anti-inflammatory activity when tested in experimental diseases. It selectively inhibits the synthesis of inflammatory C-C chemokines including CCL2, CCL7 and CCL8. This work aims to analyse bindarit effects on ET1-, AngII- and TGFβ-induced mesangial cell dysfunction. Bindarit significantly reduced AngII-, ET1- and TGFβ-induced α-SMA upregulation. In a collagen contraction assay, bindarit reduced AngII-, ET1- and TGFβ-induced HRMC contraction. Within 3–6 h stimulation, vinculin organization and phosphorylation was significantly impaired by bindarit in AngII-, ET1- and TGFβ-stimulated cells without any effect on F-actin distribution. Conversely, p38 phosphorylation was not significantly inhibited by bindarit. Our data strengthen the importance of CCL2 on ET-1, AngII- and TGFβ-induced mesangial cell dysfunction, adding new insights into the cellular mechanisms responsible of bindarit protective effects in human MC dysfunction.